Geoprocessamento aplicado na caracterização morfométrica da microbacia do Ribeirão Descalvado – Botucatu, SP - Campos, Sérgio [UNESP]; Felipe, Andrea Cardador [UNESP]; Campos, Marcelo [UNESP]; Reche, Aline Minarelli [UNESP] (My University, 2015)
The objective of this study was to evaluate geoprocessing to morphometrically characterize the Ribeirão Descalvado micro watershed – Botucatu, SP by the Geographic Information System (GIS) – Selva for preservation, rationalization of its use and environmental restoration. The micro watershed is 2,228.61 ha between the geographic coordinates: 22° 50' 05 to 22° 54' 26 latitude S and 48° 22' 29 to 48° 26' 36 longitude W Gr. The cartographic basis was the planialtimetric chart of Botucatu (SP), 1: 50000 scale (IBGE, 1969), used for extraction of level, hydrography and topography curves to determine morphometric indices. The results showed that low values of drainage density associated with the presence of permeable rocks facilitates ground water infiltration which decreases surface runoff, erosion risks and environmental degradation. The low value of the shape factor supported by the circularity index shows that the micro watershed is more elongated and at lower risk of more pronounced floods. The roughness coefficient environmental parameter classified the micro watershed for forest and reforestation.
Geoprocessing applied to morphometric characterization of the stream Descalvado watershed - Botucatu, SP
Keywords: Hydrography and GIS; Morphometry